1980
DOI: 10.3177/jnsv.26.279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postnatal undernutrition on the catecholamine and serotonin contents of suckling rat brain.

Abstract: SummaryThe effect of postnatal undernutrition on the catecholamine and serotonin contents of various parts of the brain of suckling rats was examined. Undernourishment was induced by increasing the litter size to 18 pups from day 1 to 21 after birth. In control pups, the total amounts of norepinephrine and dopamine in the whole brain increased greatly during the suckling period (norepinephrine: 17.7ng at birth, 154ng on day 10, and 420ng on day 21; dopamine: 12.6ng at birth, 269ng on day 10, and 1,022ng on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…Facchinetti et al (1993) demonstrated that prolonged neonatal treatment (PD 1-22) of the NMDA receptor through a noncompetitive (MK-801) or competitive (CGP 39551) antagonist increased spontaneous locomotor activity on PD 28 and this increase continued to PD 60. Neonatal malnutrition can affect the neurochemical markers of dopaminergic function in the brain, such as dopamine content or tyrosine hydroxylase activity (Hisatomi and Niiyama, 1980;Ramanamurthy, 1977;Sobotka et al, 1974). Their findings were in contrast with those of our behavioral study, in which neonatal PCP reduced MAP-induced stereotyped behavior.…”
Section: Effect Of Neonatal Pcp On Map-induced Stereotypycontrasting
confidence: 99%
“…Facchinetti et al (1993) demonstrated that prolonged neonatal treatment (PD 1-22) of the NMDA receptor through a noncompetitive (MK-801) or competitive (CGP 39551) antagonist increased spontaneous locomotor activity on PD 28 and this increase continued to PD 60. Neonatal malnutrition can affect the neurochemical markers of dopaminergic function in the brain, such as dopamine content or tyrosine hydroxylase activity (Hisatomi and Niiyama, 1980;Ramanamurthy, 1977;Sobotka et al, 1974). Their findings were in contrast with those of our behavioral study, in which neonatal PCP reduced MAP-induced stereotyped behavior.…”
Section: Effect Of Neonatal Pcp On Map-induced Stereotypycontrasting
confidence: 99%
“…However, studies of central catecholaminergic mechanisms suggest that abnormal nutritional status has a substantial deleterious effect on neuronal and synaptic function. During dietary restriction, norepinephrine levels and some indices of neuronal activity show moderate degrees of attenuation (4)(5)(6)(7)(8); although whole brain norepinephrine levels tend to be restored to normal in adulthood (9-1 I), there are at least two reports that deficits in receptor binding sites and synaptic activity may persist if malnutrition is maintained into adulthood (12,13).…”
mentioning
confidence: 99%
“…While most studies have found an increase in serotonin concentration [23][24][25][26][27] others have reported a decrease or no change in undernourished rodents or humans. 11,12,28,29) In addition, previous studies have shown that PM causes a reduction in 5-HT 1A binding 12) and hyporeactivity to 5-HT 1A receptor agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Although the influence of early postnatal undernutrition on the serotonergic systems has been the subject of considerable biochemical research, [23][24][25] the data on brain serotonin content in early undernourishment is conflicting. While most studies have found an increase in serotonin concentration [23][24][25][26][27] others have reported a decrease or no change in undernourished rodents or humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation